The Role of Tarekat Naqsabandiyah in Building Socio-Cultural Communication Among the Congregation of Surau Syukurul Amin Kabanjahe Karo District - Ginting, Dwiva Ramadani; Muniruddin, Muniruddin (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2025)
AbstractThis study aims to examine the role of the Naqsabandiyah Order in building socio-cultural communication among the congregation of Surau Syukurul Amin, Kabanjahe, Karo Regency. Using a qualitative approach and case study method, this study explores how spiritual practices, such as dhikr, wirid, and suluk, carried out in Surau Syukurul Amin, not only strengthen the religious dimension but also form patterns of social and cultural interaction among the congregation, who come from heterogeneous cultural backgrounds. Data were obtained through observation, in-depth interviews, and documentation of the leaders of the surau, as well as key figures, using purposive sampling techniques. Data analysis was conducted using the Miles and Huberman model, which involves three stages: data reduction, data presentation, and conclusion. The results of the study indicate that the Naqsabandiyah Order plays a role in building socio-cultural communication among the congregation, as a mediator between universal Islamic values and local wisdom of the Karo community, strengthening solidarity, socio-cultural identity, and creating harmony and togetherness in the congregation environment. The practice of tarekat practices such as tawajjuh, wirid, and suluk not only strengthens spiritual relationships with Allah but also strengthens social communication, builds empathy, cooperation, and tolerance among members of the congregation. The socio-cultural communication formed among the congregation of the Naqsyabandiyah Tarekat of Surau Syukurul Amin Kabanjahe is very positive and harmonious. This can be seen from various aspects such as: (1) Significant social and cultural changes. (2) Acceptance and Adaptation of Local Culture. (3) Equality and Solidarity Between Congregations. (4) Good resolution of social problems. (5) Communication with the outside community. (6) Handling Communication Challenges. Based on several aspects, the socio-cultural communication formed among the congregation of the Naqsyabandiyah Tarekat of Surau Syukurul Amin Kabanjahe shows very positive and harmonious dynamics. The communication patterns that are built are not only limited to spiritual aspects, but have developed into a social interaction system that prioritizes the values of togetherness, equality, and mutual understanding among members of the congregation. Keywords: Communication, Naqsabandiyah, Socio-Cultural, Surau Syukurul Amin, Tarekat. AbstrakPenelitian ini bertujuan untuk mengkaji peran Tarekat Naqsabandiyah dalam membangun komunikasi sosial budaya di kalangan jama’ah Surau Syukurul Amin, Kabanjahe, Kabupaten Karo. Dengan menggunakan pendekatan kualitatif dan metode studi kasus, penelitian ini mengeksplorasi bagaimana praktik-praktik spiritual seperti zikir, wirid, dan suluk yang dijalankan di Surau Syukurul Amin tidak hanya memperkuat dimensi religius, tetapi juga membentuk pola interaksi sosial dan budaya di antara jama’ah yang berasal dari latar belakang budaya yang heterogen. Data diperoleh melalui observasi, wawancara mendalam, dan dokumentasi terhadap pimpinan surau, serta tokoh-tokoh kunci menggunakan teknik purposive sampling. Analisis data dilakukan dengan model Miles dan Huberman melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa Tarekat Naqsabandiyah berperan dalam membangun komunikasi sosial budaya jama’ah, sebagai mediator antara nilai-nilai Islam universal dan kearifan lokal masyarakat Karo, memperkuat solidaritas, identitas sosial budaya, serta menciptakan harmoni dan kebersamaan di lingkungan jama’ah. Praktik amalan tarekat seperti tawajjuh, wirid, dan suluk tidak hanya mempererat hubungan spiritual dengan Allah, tetapi juga memperkuat komunikasi sosial, membangun empati, gotong royong, dan toleransi di antara anggota jama’ah. Komunikasi sosial budaya yang terbentuk di kalangan jama’ah Tarekat Naqsabandiyah Surau Syukurul Amin Kabanjahe sangat positif dan harmonis hal ini dapat dilihat dari berbagai aspek seperti; (1) Perubahan sosial dan budaya yang signifikan. (2) Penerimaan dan Adaptasi Budaya Lokal. (3) Kesetaraan dan Solidaritas Antar Jamaah. (4) Penyelesaian masalah sosial yang baik. (5) Komunikasi dengan masyarakat luar. (6) Penanganan Tantangan Komunikasi. Berdasarkan beberapa aspek tersebut, komunikasi sosial budaya yang terbentuk di kalangan jamaah Tarekat Naqsyabandiyah Surau Syukurul Amin Kabanjahe menunjukkan dinamika yang sangat positif dan harmonis. Pola komunikasi yang dibangun tidak hanya terbatas pada aspek spiritual semata, tetapi telah berkembang menjadi suatu sistem interaksi sosial yang mengedepankan nilai-nilai kebersamaan, kesetaraan, dan saling pengertian di antara anggota jama’ah. Kata Kunci : Komunikasi, Naqsabandiyah, Sosial Budaya, Surau Syukurul Amin, Tarekat.